2006
DOI: 10.1109/tdsc.2006.41
|View full text |Cite
|
Sign up to set email alerts
|

System Call Monitoring Using Authenticated System Calls

Abstract: System call monitoring is a technique for detecting and controlling compromised applications by checking at runtime that each system call conforms to a policy that specifies the program's normal behavior. Here, we introduce a new approach to implementing system call monitoring based on authenticated system calls. An authenticated system call is a system call augmented with extra arguments that specify the policy for that call, and a cryptographic message authentication code that guarantees the integrity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…By positioning the rewritten versions of these two functions at those addresses, the rewriter can encode overlapping pointers to them in the lookup table. With chunk size c = 16 and memory division d = 2 28 , a rewritten code base address of 2 24 (t & 0xF) + 2 16 t supports at least 15 two-pointer collisions and 1 three-pointer collision per rewritten code page-far more than we saw in any binary we studied.…”
Section: Code Conventionsmentioning
confidence: 73%
See 1 more Smart Citation
“…By positioning the rewritten versions of these two functions at those addresses, the rewriter can encode overlapping pointers to them in the lookup table. With chunk size c = 16 and memory division d = 2 28 , a rewritten code base address of 2 24 (t & 0xF) + 2 16 t supports at least 15 two-pointer collisions and 1 three-pointer collision per rewritten code page-far more than we saw in any binary we studied.…”
Section: Code Conventionsmentioning
confidence: 73%
“…Past work [17,19,28] has shown that IRM systems are capable of enforcing more sophisticated temporal properties when equipped with more powerful event languages and responses to impending policy violations that go beyond mere program termination. Developing policy-enforcement libraries that implement such policies is therefore a logical next step toward applying our framework to interesting, practical security problems for these real-world systems.…”
Section: Other Future Workmentioning
confidence: 99%
“…In addition, they apply binary rewriting to assign unique names to call sites, to further curb nondeterminism in the monitor (an analogous technique, call-signing, is presented by Rajagopalan et. al [26]). Because invocations of xhr are, however, often deep within frameworks, signatures cannot be placed at invocations of that function; they must instead be "pushed up" the call chain to where the requests are really made.…”
Section: Related Workmentioning
confidence: 96%
“…Other systems use a model of calls constructed through static analysis [33,7,12,26]. These systems all address operating system monitoring, where the operating system (corresponding to our server), monitor, and application (corresponding to our browser client) all run on the same machine.…”
Section: Related Workmentioning
confidence: 99%
“…A more usable MAC solution is described in [16]. A cryptographic-based MAC system is the authenticated system call work by Rajagopalan et al [22], which is closed in spirit to our A2 framework. The presented work in the authenticated system call is limited to providing identities (the HMAC) to individual function calls to system calls in an application.…”
Section: Related Workmentioning
confidence: 99%